El conocimiento divino de los males según Tomás de Aquino = Abweichender Titel: The divine knowledge of evil according to Thomas Aquinas - Moros, Enrique R. (Cauriensia, 2025)
In the philosophy of Saint Thomas Aquinas, we can find insights into what is most difficult: divine knowledge of evil. To do so, it is necessary to delve into a sea of distinctions that are almost unknown to contemporary philosophy. For this reason, we will examine whether the divine idea of evil is possible to demonstrate that God has no idea of evil, but that God has a merely speculative knowledge of all evil. Secondly, we will delve into the divine will to determine whether God can, in any way, will evil, whether physical or moral. And we will conclude with an exposition of the idea of Good, which is essential for the metaphysics of creation and for anthropology.